Why Are So Many Western Intellectuals Abandoning Liberalism and What Can We Do About It? - Aurelian Craiutu (Journal of Contextual Economics – Schmollers Jahrbuch, 2022)
This article analyzes some of the reasons why so many Western intellectuals have seemed ready to abandon the principles of liberalism lately in search for alternative solutions. I begin by examining the fascination exercised by Viktor Orbán among conservatives in the US who emerged as staunch critics of liberalism. Next, I show that the doom industry has a long history and discuss the conceptual fluidity of liberalism and its implications for students of liberalism. I argue that by acknowledging the polysemantic nature of liberalism we can better answer its critics. I draw on the lessons of German Ordoliberals to show that liberalism contains surprising resources neglected by its critics. The article concludes with a call to moderate liberalism inspired by Karl Popper's defense of the open society.
Keywords: F63; P10; P16; 330; Karl Popper; Mont Pelerin Society; Liberalism; Death of Liberalism; Conservatism; Open Society; Bourgeois Virtues; Viktor Orbán; Wilhelm Röpke